Development of a QR code-based traditional music e-module to improve instrumental skills and cultural literacy - Sylvia Oktari; Heldi Heldi; Indrayuda Indrayuda; Tulus Handra Tulus Handra (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
This research created a traditional musical instrument skills and cultural literacy enhancement e-module through the use of a QR Code for music learning at vocational high schools. The research was carried out as the learning resources were scarce, causing fewer opportunities for self-practice and less understanding of the cultural values in traditional music. Repeated, self-paced, and QR-linked audiovisual exposure sessions were considered a great means to reinforce the technical work of the students and at the same time deepen their understanding of the context and the culture of each piece, thus establishing a theoretical connection between the technology and the two dependent variables. The research and development method with the ADDIE model was used for the study, using a one-group pretest-posttest design without a control group. The participants were [insert exact number] purposively selected Grade X vocational high school students along with material and media experts, and a music teacher. Data collection instruments were expert validation sheets, practicality questionnaires, learning achievement tests, instrumental performance assessments, and cultural literacy questionnaires, with the questionnaire instruments' internal consistency measured by Cronbach's Alpha (α = [insert coefficient]). Results demonstrated that the e-module Material expert and media expert determined validity to be approximately 94.0% each and practicality levels teacher = 93.4%; students = 91.2% were very high, its implementation also enhanced students' learning achievements (pretest-posttest N-Gain = 0.65, medium-to-high category), instrumental skills 87.25%, and cultural literacy (90.75 %). The use of QR Code technology allowed students to easily access multimedia learning resources and encouraged independent learning. The final developed e-module was hence found to be a valid, practical, and effective digital learning resource for traditional music instruction.